2009
DOI: 10.1016/j.bbi.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of psychological and immune stressors on inflammatory cytokine and sickness responses in humans

Abstract: Activation of the innate immune system is commonly accompanied by a set of behavioural, psychological and physiological changes known as ‘sickness behaviour’. In animals, infection-related sickness symptoms are significantly increased by exposure to psychosocial stress, suggesting that psychological and immune stressors may operate through similar pathways to induce sickness. We used a double-blind, randomised, placebo-controlled design to examine the effect of acute psychological stress on immune and subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 37 publications
8
111
3
3
Order By: Relevance
“…In the present study, no effect of inflammatory stress on mood was found in controls; however, other studies [17,19,20,40,41,42,43], although not all [44], observed negative effects of inflammation in healthy controls. Interestingly, personality traits such as optimism protect against inflammation-induced mood decreases [45].…”
Section: Discussioncontrasting
confidence: 52%
“…In the present study, no effect of inflammatory stress on mood was found in controls; however, other studies [17,19,20,40,41,42,43], although not all [44], observed negative effects of inflammation in healthy controls. Interestingly, personality traits such as optimism protect against inflammation-induced mood decreases [45].…”
Section: Discussioncontrasting
confidence: 52%
“…In particular, stress is an important confounding factor because it induces an increase in pro-inflammatory cytokine levels in the blood. 129,130 This result has also been demonstrated for depression, which has been associated with disturbances in pro-inflammatory cytokine levels and circulating immune cells. 121,122 In addition, disturbances in trypto-phan metabolism have been described in affective disorders [131][132][133] and are thus very likely to impact 5HT levels.…”
Section: Limitations and Further Directionssupporting
confidence: 53%
“…Recent reports indicate that acute psychosocial stressors were found to upregulate protective cytokine and protective behavioral responses to immune stimuli in rodents [22,23] . However, psychological and immune stressors can also act synergistically to promote inflammation and sickness behavior in humans which ultimately can be, if self-limited, protective to the host [24] . Cytokines mediate and control immune and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%